Brexit, private equity and management - Wright, Mike; Wilson, Nick; Gilligan, John; Bacon, Nick; Amess, Kevin (Wiley, 2016)
We analyse the expected impact of Brexit on private equity and its implications for management research. Specifically, we explore the implications for PE funds and funding, and at the portfolio firm level with respect to employment and performance.